2018
DOI: 10.1111/1462-2920.14393
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivities of microbial plankton net growth rates are seasonally coherent and linked to nutrient availability

Abstract: Recent work suggests that temperature effects on marine heterotrophic bacteria are strongly seasonal, but few attempts have been made to concurrently assess them across trophic levels. Here, we estimated the temperature sensitivities (using activation energies, E) of autotrophic and heterotrophic microbial plankton net growth rates over an annual cycle in NE Atlantic coastal waters. Phytoplankton grew in winter and late autumn (0.41 ± 0.16 SE d ) and decayed in the remaining months (-0.42 ± 0.10 d ). Heterotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 75 publications
(127 reference statements)
8
37
1
Order By: Relevance
“…With regard to LNA cells, their negative specific growth rates in Mangrove and Seagrass became more negative with warming yielding equivalent E values of ca. −1 eV (see a more detailed discussion in the study by Morán et al ., ). Similar to the previous consideration, Dead cells cannot really have an activation energy, but we compared their apparent E values in order to assess their dynamics in response to temperature.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…With regard to LNA cells, their negative specific growth rates in Mangrove and Seagrass became more negative with warming yielding equivalent E values of ca. −1 eV (see a more detailed discussion in the study by Morán et al ., ). Similar to the previous consideration, Dead cells cannot really have an activation energy, but we compared their apparent E values in order to assess their dynamics in response to temperature.…”
Section: Resultsmentioning
confidence: 97%
“…S5A). The same response has been recently reported for temperate phytoplankton under nutrient limitation (Morán et al ., ), suggesting that warming would exacerbate any metabolic and ecological processes resulting in either growth or decay of the various bacterial groups initially present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the short‐term incubations carried out in this study, we found that experimental warming noticeably increased the abundance of microphytoplankton‐associated bacteria, while the effect on the free‐living community was less pronounced. Such larger effect of associated bacteria may be explained by at least two mechanisms: (i) increased chemotaxis ability to newly fixed DOC by the microphytoplankton‐associated bacteria (Smriga et al ., 2016), which would also promote a faster response to warming as the temperature sensitivity of bacteria is strongly related to the availability of resources (López‐Urrutia and Morán, 2007; Berggren et al ., 2010; Morán et al ., 2018), and/or (ii) a higher exudation of organic compounds by diatoms at higher temperatures, including transparent exopolymers particle (Claquin et al ., 2008; Wohlers et al ., 2009; Seebah et al ., 2014), which would facilitate bacterial aggregation (Mari and Kiørboe, 1996; Gardes et al ., 2011). In any case, we found that the impact of experimental warming was distinct for the entire associated bacterial community in comparison to the two taxa analysed and that it also exerted a noticeable larger effect on Flavobacteria than on Rhodobacteraceae, indicating a differential response of both taxonomic groups in terms of abundance, as previously observed in free‐living communities (von Scheibner et al ., 2014; Arandia‐Gorostidi et al ., 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of BAC, the increase in temperature in May (from 21°C to 24°C) and July (from 23.6°C to 26.6°C) caused an increase in the growth rate only in the +P condition, which is supported by the study of Morán et al . () who found that the rise in temperature stimulates growth only in conditions of sufficient nutrients. This is particularly pronounced at temperatures above the optimal when bacterial growth slows down or stops.…”
Section: Discussionmentioning
confidence: 99%